GAMBARAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN PT. POS KANWIL MEDAN - sarmaulina simangunsong; Nancy Naomi Aritonang; Hotpascaman Simbolon (Universitas HKBP Nommensen, 2022)
Organizational Citizenship Behavior (OCB) is important for employees in an organization, because employees with high OCB, namely by showing behavior to help other employees (altruism), voluntary participation and support for organizational functions both professionally and socially natural (civic virtue), personal awareness to work beyond minimum standards (conscientiousness), behavior to alleviate work-related problems faced by others (courtesy) and not to create damaging issues despite feeling irritated (sportsmanship). Research conducted on 60 employees at the PT. Pos Kanwil Medan, which was conducted using total sampling technique, found that Organizational Citizenship Behavior (OCB) among PT. Pos Kanwil Medan are in the moderate category (53.3%), and ​​in high category (46.7%).